Three-dimensional reconstruction and measurement of fuel assemblies for sodium-cooled fast reactor using linear structured light. (15th September 2021) - Zhao, Jianping; Feng, Chang; Cai, Gen; Zhang, Run; Chen, Zhibo; Cheng, Yong; Xu, Bing
Highlights: A three dimensional reconstruction and measurement system of fuel assembly based on linear structured light with radiation resistance is proposed. The measurement error which is introduced by the refraction effects at the air-glass interface, is corrected by the refractive correction model. A contour splicing method to unify the data obtained by four linear structured light measuring instruments into a world coordinate system is put forward. Abstract: Three-dimensional reconstruction and measurement of sodium-cooled fast reactor fuel assemblies has played an important role in evaluating the deformation and mechanical damage of sodium-cooled fast reactor fuel assemblies and judging whether they can continue to be used. In this paper, a three-dimensional reconstruction and measurement method for the fuel assemblies of sodium cooled fast reactor based on linear structured light with radiation resistance is proposed.Then, the measurement error is corrected by the refractive correction model, which is introduced by radiation resistant glass. What's more, a contour splicing method to unify the data obtained by four linear structured light measuring instruments into a world coordinate system is put forward.The effect of radiation resistant glass on measurement accuracy was tested, and the measurement results are corrected with a correction error of ± 0.05 mm.The three-dimensional reconstruction and measurement of a standard part and a simulation component of sodium-cooled fast reactor fuel assembly shows that the method can achieve high-precision 3D reconstruction, and the measurement error of the opposite margin and the diagonal distance of the standard part is less than ± 0.05 mm.